The Effect of Quality Tracing System on Safety of Agricultural Product. (16th February 2015) - Zhao, Jun; Zhou, Bin
Abstract : Frequent occurrence of food safety incidents in recent years has made analyzing safety of agricultural product in view of contract theory become academic research focus. Based on incentive theory, in this paper we establish a static game under the condition of asymmetric information and analyze how the "company + farmer" contract is influenced by a complete quality tracing system composed of ex-ante inspection and ex-post traceability. Meanwhile, we find out that a complete quality tracing system can increase the safety level of agricultural product and that ex-ante inspection and ex-post traceability can replace each other in the process. Finally, we put forward policy suggestion for the policy-maker to solve the problem of food safety.